A geometry problem by Tanishq Varshney

Geometry Level 3

Consider a point P P on the line y = x y=x and two fixed point A ( 3 , 4 ) A(3,4) and B ( 6 , 13 ) B(6,13) .Then find P P such that P A + P B PA+PB is minimum.

( 9 4 , 9 4 ) \left(\frac {9}4, \frac {9}4 \right) ( 15 2 , 15 2 ) \left(\frac {15}2, \frac {15}2 \right) ( 5 2 , 5 2 ) \left(\frac {5}2, \frac {5}2 \right) ( 17 4 , 17 4 ) \left(\frac {17}4, \frac {17}4 \right)

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Tanishq Varshney
Dec 25, 2014

take the image of point p in the line y=x which comes out to be A (4,3) using congruent triangles u can see that PA=PA Now take a point p ony=x say (t,t) from the slope we have slope of A B=PB solve for t A is the image of A in y=x. we cannaot take point P1 as PA+PB will not be minimum. also tr(APM) is congruent to tr(A*PM) by SAS RULE.

Elaborate it

Ankit Jain - 6 years, 5 months ago

I have tried this problem out in two different ways: Firstly graphically. The locus of points that have PA+PB constant is an ellipse with points A and B as its focuses. To minimise the size of PA+PB we need to find the smallest ellipse that will just touch the line y=x; Constructing this graphically in a CAD package shows the tangent being very close to (17/4,17/4).

Secondly algebraically: since x=y on the line we can substitute x for y and get;

PA + PB is ( x 3 ) 2 + ( x 4 ) 2 + ( x 6 ) 2 + ( x 13 ) 2 \sqrt{(x-3)^2 + (x-4)^2} + \sqrt{(x-6)^2+(x-13)^2}

differentiating the above, then considering only the numerator, gives

( x 7 ) 2 x 2 38 x + 205 + ( x 19 ) 2 x 2 14 x + 25 (x-7)\sqrt{2x^2-38x+205} + (x-19)\sqrt{2x^2-14x+25}

this must be zero at the point where AP+BP is a minimum (or maximum), and it can be solved numerically to be exactly 17/4.

Ed Sirett - 4 years, 8 months ago

Since P P is on the line y = x y=x , let its coordinates be P ( x , x ) P(x,x) . The shortest P A + P B PA+PB is when P A PA is an incident light ray and P B PB the reflected light ray at point P P on the mirror y = x y=x as shown in the figure. Since the incident angle equals to the reflective angle, the angle P A PA makes with y = x y=x is the same as P B PB makes with y = x y=x and equals to θ \theta . Then the gradients of P A PA and P B PB , m A m_A and m B m_B respectively are given by:

{ m A = tan ( π 4 θ ) = x 4 x 3 θ = π 4 tan 1 ( x 4 x 3 ) m B = tan ( π 4 + θ ) = x 13 x 6 θ = tan 1 ( x 13 x 6 ) π 4 \begin{cases} m_A = \tan \left(\dfrac \pi 4 - \theta\right) = \dfrac {x-4}{x-3} & \implies \theta = \dfrac \pi 4 - \tan^{-1} \left(\dfrac {x-4}{x-3} \right) \\ m_B = \tan \left(\dfrac \pi 4 + \theta\right) = \dfrac {x-13}{x-6} & \implies \theta = \tan^{-1} \left(\dfrac {x-13}{x-6} \right) - \dfrac \pi 4 \end{cases}

π 4 tan 1 ( x 4 x 3 ) = tan 1 ( x 13 x 6 ) π 4 π 2 tan 1 ( x 4 x 3 ) = tan 1 ( x 13 x 6 ) cot 1 ( x 4 x 3 ) = tan 1 ( x 13 x 6 ) tan 1 ( x 3 x 4 ) = tan 1 ( x 13 x 6 ) x 3 x 4 = x 13 x 6 ( x 3 ) ( x 6 ) = ( x 13 ) ( x 4 ) x 2 9 x + 18 = x 2 17 x + 52 8 x = 34 x = 17 4 \begin{aligned} \implies \frac \pi 4 - \tan^{-1} \left(\frac {x-4}{x-3} \right) & = \tan^{-1} \left(\frac {x-13}{x-6} \right) - \frac \pi 4 \\ \frac \pi 2 - \tan^{-1} \left(\frac {x-4}{x-3} \right) & = \tan^{-1} \left(\frac {x-13}{x-6} \right) \\ \cot^{-1} \left(\frac {x-4}{x-3} \right) & = \tan^{-1} \left(\frac {x-13}{x-6} \right) \\ \tan^{-1} \left(\frac {x-3}{x-4} \right) & = \tan^{-1} \left(\frac {x-13}{x-6} \right) \\ \frac {x-3}{x-4} & = \frac {x-13}{x-6} \\ (x-3)(x-6) & = (x-13)(x-4) \\ x^2 - 9x + 18 & = x^2 - 17x + 52 \\ 8x & = 34 \\ \implies x & = \frac {17}4 \end{aligned}

Therefore, P ( 17 4 , 17 4 ) P\boxed{\left(\frac {17}4, \frac {17}4\right)} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...